2019
DOI: 10.1370/afm.2363
|View full text |Cite
|
Sign up to set email alerts
|

The Practice Gap: National Estimates of Screening and Counseling for Alcohol, Tobacco, and Obesity

Abstract: Tobacco use, lack of physical activity and poor diet, and alcohol consumption are leading causes of death in the United States. We estimated screening and counseling rates by using a nationally representative sample of adults aged 35 years and older with a preventive care supplement to the 2014 Medical Expenditure Panel Survey. Receipt of the recommended level of services ranged from nearly two-thirds (64.2% for obesity, 61.9% for tobacco use) to less than one-half (41.0% for alcohol misuse). There is signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…An irregular dieting increases the burden on the body (15). For instance, skipping breakfast on weekends for an extended period may be bad for the digestive system (16). A result of study in South Africa indicated that irregular consumption of weekday breakfasts was associated with an increased risk of being overweight and obese among adolescents (15).…”
Section: Discussionmentioning
confidence: 99%
“…An irregular dieting increases the burden on the body (15). For instance, skipping breakfast on weekends for an extended period may be bad for the digestive system (16). A result of study in South Africa indicated that irregular consumption of weekday breakfasts was associated with an increased risk of being overweight and obese among adolescents (15).…”
Section: Discussionmentioning
confidence: 99%
“…Failure to address comorbid psychiatric comorbidities, which are common in the setting of substance use disorders, also limits detection and treatment (30). The difficulties in screening for AUD and its end-organ manifestations are reinforced by studies showing that less than half of American adults are receiving recommended screening for alcohol misuse and that ALD is diagnosed at a later stage compared with other etiologies of liver disease (31,32). In addition to issues with underdiagnosis, treatments are limited in ALD.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found that the largest weight losses were achieved with high-intensity counseling by PCPs and referral of interested individuals to appropriate interventions [ 9 - 13 ]. However, a study of a nationally representative sample of adults aged 35 years and older found that, despite more adults reported being screened for obesity (78.6%) and of those screened, nearly 40% had a BMI of 30 kg/m 2 or higher (39.2%), only slightly more than one-half (53.5%) of obese adults screened reported receiving counseling about weight management [ 14 ]. Furthermore, BMI is the most preferred screening tool, though literature indicates it could be a poor indicator of cardiovascular disease and overall mortality risk [ 7 , 15 ].…”
Section: Introductionmentioning
confidence: 99%